Integral Methodology in Geospatial Researches - Eugene Nikolaevich Eremchenko; Vladimir Aleksandrovich Kolosov; Vladimir Sergeevich Tikunov (Наука. Инновации. Технологии)
Introduction. The task of developing the methodology optimal for studying unique processes and phenomena, especially in the light of the growing awareness of the globality of our planet and the integrity of processes – for example, biological and social – is formulated. Special importance and heuristic value of this kind of methodology is pointed out because of the special status of the categories of space and time, as the cognizing subject perceives the external reality only through space and time and in no other way (I. Kant). Materials and research methods. The article substantiates the necessity of the use of integral or integral space-time methodology for the scientific analysis of unique phenomena (for example, biological phenomena). This methodology supplements the widely used differential methodology. It is stated that this task is currently of particular relevance. It is emphasized that integral methodology is doctrinally close to philosophy, scientific theory and intellectual tradition of holism. The results of research and their discussion. The example of successful use of integral methodology in another disciplinary field by Hans Selye in discovering stress, or general adaptation syndrome, in the first half of the twentieth century is considered and analyzed. A conclusion is made about the possibility of fruitful application of this method in other problem areas, in interdisciplinary research and, in particular, in geospatial research when combined with the fundamentally integral concept of the Digital Earth and the Big Data method. The possibility of using the integral method in spatial studies for the reduction of Big Data without losing their heuristic value is considered. It is expedient to use the proposed method in the analysis of biomedical, ecological and social processes, particularly in the early stages of the pandemic COVID-19, the global dynamics of which was first recorded in world history with high accuracy.Conclusions. The prospect of using the integral method in geospatial research is briefly summarized. It is pointed out that integral method can be successfully applied for testing of various hypotheses about the  nature of the COVID-19 pandemic by Popper's method.